COMPARATIVE ANALYSIS OF IMPULSE BUYING BASED ON GENDER DIFFERENCES - Tulungen, Christina Ester (Jurnal EMBA: Jurnal Riset Ekonomi, Manajemen, Bisnis dan Akuntansi, 2013)
Consumer Buying Decision is one important indicator for the actual impulse buying from customers in the marketplace and is influenced by Emotion, Life Style, Factor Situational and Promotion. This research is purposed to analyze the differences of impulse buying between male and female in Manado. This research used the Independent sample t-test as the method of this research.  Population in this research is mainly in this research is people in Manado. The sample of this research is 100 respondents of random sampling. Impulse Buying of male is statistically significant difference with Impulse Buying of female in Manado. Impulse Buying of female is higher than male in Manado, when female have higher Emotion, Life Style, Factor Situational and Promotion that can increase their impulse buying. The interpretation shows that the mean between male and female is different and supported by significance level of the p-value. Keywords: impulse buying, gender, buying decision